THE STRUCTURE OF SPEECH ACTS IN VARIOUS TYPES OF DISCOURSE (Scientific journal of the Fergana State University, 2024)
This paper examines the structure of speech acts in various types of discourse, including formal, informal, persuasive, and informative. It explores how different types of discourse shape the structure of speech acts and impact their effectiveness in communication. The study also discusses the role of context, cultural norms, and social dynamics in shaping speech act structures.